Substituted pyrazolo[3,4-d]pyrimidines : microwave assisted, solvent free synthesis and biological evaluation - Campos, Ana M. F. Oliveira (2008)
A simple and efficient method has been developed for the synthesis of various pyrazolo[3,4-d]pyrimidines using microwave irradiation under solvent-free conditions. The advantages of applying microwave irradiation compared with the classical method were demonstrated. The structures of all the compounds were confirmed by the usual techniques and in two cases by X-ray analysis. The compounds did not display appreciable ability to inhibit xanthine oxidase activity. Screening for antifungal activity showed that some derivatives were active against four fungi, with more significant results for Botrytis.